Au‐Promoted Pt nanoparticles supported on MgO/SBA‐15 as an efficient catalyst for selective oxidation of glycerol. Issue 6 (28th January 2021) - Liu, Yibin; Zha, Minghao; Qin, Hansong; Yao, Shuang; Zhou, Xin; Zhao, Siming; Sheng, Nan; Sun, Yinghao; Jin, Xin; Yan, Hao; Feng, Xiang; Chen, Xiaobo; et al.
Abstract: A systematic study of Au‐promoted and unpromoted Pt/MgO/SBA‐15 catalyst is developed to separate the promoter effect from electron transfer effect between Au and Pt. Multi‐characterizations revealed that Au and Pt metals in these bimetallic catalysts mainly exist in the form of alloy, and the main role of Au is to reduce the size of AuPt alloy nanoparticles, thus enhancing the adsorption and activation of intermediate products. Through the optimization of various factors (including MgO content, Au/Pt molar ratio, reaction temperature and time), the Au1 Pt2 /MgO/SBA‐15 (0.05) catalyst exhibits excellent catalytic activity and glyceric acid selectivity for the selective oxidation of glycerol. Density functional theory calculation confirmed that the synergistic effect between Pt and Au active sites could facilitate the oxidation of primary hydroxyl group by promoting the activation of CH bond and the oxidation of aldehyde group. The results may give insights on designing effective Pt based bimetallic catalyst for selective oxidation of glycerol. Abstract : We systematically investigated the promotion role of AuPt bimetallic nanoparticles supported on MgO/SBA‐15 for base‐free oxidation of glycerol to glyceric acid. A high turnover frequency of 831.5 hr −1 together with 69.7% glyceric acid selectivity was obtained on the Au1 Pt2 /MgO/SBA‐15 (0.05) catalyst with small AuPt alloy nanoparticles.